Emergent eukaryotic directional sensing via receptor degradation and diffusion - Andrew Goetz; Purushottam Dixit (Proceedings of the National Academy of Sciences, 2025)
Directional sensing enables eukaryotic cells to detect spatial gradients of extracellular ligands, allowing them to orient and migrate within complex environments. Prevalent models explain this computation through a circuit where signaling species with distinct diffusion constants act incoherently on a downstream readout. Here, we propose a fundamentally different mechanism of directional sensing based on simple receptor-level processes. Our model integrates three ubiquitous receptor processes-lateral diffusion, basal ligand-independent activation, and active receptor degradation, THAT together synergize to generate robust directional sensing. In the absence of diffusion, active receptor degradation and basal activity implement an integral feedback that adapts active receptor levels to a ligand-independent set point while depleting receptors in relatively ligand-rich regions. Diffusion then redistributes receptors from regions of relatively low ligand exposure to regions with higher ligand exposure. This creates a spatial mismatch between activity and feedback that drives asymmetric receptor activity relative to the set point. The model predicts an optimal diffusion constant that maximizes polarization, reveals that receptors can encode relative rather than absolute ligand concentrations, and identifies the optimal basal activity that maximizes the signal-to-noise ratio in stochastic regimes. A survey of kinetic parameters across receptor families suggests that this diffusion-degradation synergy constitutes a broadly applicable, receptor-level mechanism for directional sensing.